Strategi Perencanaan Sumberdaya Usaha Produk Olahan Jamur Siswa Smk Plus Umar Zahid Semelo Bandar Kedungmulyo Jombang - Lina Susilowati; Nanik Sri Setyani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
The purpose of this study was to determine the strategic planning of business resources for processed mushroom products for students of SMK Plus Umar Zahid Semelo Bandarkedungngmulyo Jombang. The research used a quantitative approach, the data collection method was a questionnaire given to keyperson. The analysis technique uses the Process Hierarchy Analysis (AHP) technique. The conclusions of the research show that the priority scale of the main alternatives in each field in the business resource planning strategy of processed mushroom products for students of SMK Plus Umar zahid Semelo Bandarkedungmulyo Jombang are: 1) the money sector is setting aside a portion of the profit to increase business capital, 2) the material sector is to make it easier to obtain cheap raw materials, 3) the method field is to hold post-production evaluations, 4) the Man field is an increase in understanding of business resources through video media, 5) the Market field is to open market opportunities through social media, 6) the Machine field through product development which has existed. Meanwhile, the priority scale of the main alternatives in 18 alternatives in all sectors is to set aside a portion of the profit to increase the amount of capital.